Analysis of Science Books for Fourth Graders in Jordan based on Next Generation Science Standards (NGSS) - Oliemat, Ayman; Al-Mashaqba, Shifa; Al-Mashaqba, Farhan (Dirasat: Educational Sciences, 2021)
The study aims to reveal the inclusion of science books for fourth grade in Jordan of the Next Generation Science Standards (NGSS). The study followed an analytical descriptive approach, where a content analysis card was built based on (NGSS) standards. The results for each of the four fields of science in the science books for fourth grade showed that the criterion for specialized ideas was available to a moderate degree in the fields of earth and space sciences and life sciences topics, and with a low score in physics and engineering design. As for the standard of scientific and engineering practices, it was widely available in the fields of physics and engineering design, and to a moderate degree in the fields of earth and space sciences, and life sciences. As for the comprehensive concepts criterion, it had a low degree of availability in the four domains. The results also showed the availability of a set of sub-indicators of the NGSS standards that are not suitable for the fourth grade science textbooks.